Records of predatory, con-specific and human induced mauls on fish from the Northeast Atlantic and Black Sea - Raykov, Violin S. (2015)
Present study aims to describe records of mauled and con-specific injures in various fish inhabiting different environment and to discuss possible impacts on fish behavior and ontogenesis. The fish specimens were collected from the Black Sea and Azores Islands (NE Atlantic). Individuals of European flounder, Pleuronectes flesus, common stingray, Dasyatis pastinaca and turbot, Scophthalmus maximus with missing dorsal and caudal fins and flesh, were found in the Black Sea. Specimens with severe mauls of the ocean sunfish, Mola mola, almaco jack, Seriola rivoliana and sargo, Diplodus sargus were recorded from the Azores Islands. All of them were caught alive and survived severe mauls caused by predators or by accidents with propellers, fishing nets. The NE Atlantic records, although possibly caused by natural predation, are more probably than not the result of negative interactions with human activity. Numerous records of mauled fish species from both regions show that the problem with adverse effects of fisheries is quite important. Predatory and con-specific injuries obviously are compatible with basic fish vital functions of described cases. The problem with negative anthropogenic interactions seems to be insufficiently investigated and need more attention by responsible managers and decision makers.